Visual hallucinations due to inhalant use: an example of dream modeling - Danışman, Mustafa; Zengin İspir, Gamze and Sezer Katar, Kübra (Journal of Dependence, 2025)
Volatile substances can induce a range of neuropsychiatric effects, including delusions and hallucinations, and can also lead to sudden death. These substances are often associated with individuals of lower socioeconomic status and are frequently depicted in the literature as being used out of hopelessness, with little attention given to their pleasurable effects. However, the various hallucinations experienced during volatile substance use may significantly contribute to their appeal. This article explores the case of a patient admitted to our clinic for treatment who, despite being older than typically expected for such substance use, continues to use volatile substances and claims to have control over and direct these experiences. The visual hallucinations reported by the patient are analyzed, drawing parallels to the concept of lucid dreams. The findings suggest that these hallucinatory experiences may act as a positive reinforcement for the patient’s continued substance use.